New physical activity spaces in deprived neighborhoods: Does it change outdoor play and sedentary behavior? A natural experiment - Mölenberg, Famke J.M.; Noordzij, J. Mark; Burdorf, Alex; van Lenthe, F.J. (Elsevier Limited, 2019)
Background: We used the introduction of dedicated physical activity (PA) spaces in Rotterdam, the Netherlands, to study the impact of reducing distance to dedicated PA spaces on outdoor play and sedentary behavior, and to evaluate if these effects were similar between population subgroups. Methods: We included 1841 Dutch children from the Generation R Study who participated at two subsequent measurement waves when the children were, on average, 6.0 and 9.7 years old. None of these children lived within 600 m of a dedicated PA space at baseline, and during follow-up 171 children became exposed to 13 new PA spaces within 600 m from home. Individual-level fixed-effects models were used to evaluate changes in distances (determined by Geographical Information Systems (GIS)) from home to the nearest new dedicated PA space, to parent-reported outdoor play and sedentary behavior. Results: The introduction of a dedicated PA space within 600 m from home, and the reduction of the distance per 100 m, did not affect outdoor play or sedentary behaviors. At p < 0.1, significant interaction terms were found between the introduction of the PA spaces and indicators of family socioeconomic position. Although not statistically significant, stratified analyses showed a consistent pattern, suggesting that reducing the distance to the nearest PA space increased outdoor play for children from parents with lower levels of education. However, they also showed a non-significant increase in sedentary behaviors for children from families with net household income below average Dutch income, and for children from a non-Dutch ethnicity. Conclusions: Introducing dedicated PA spaces may be a promising approach to increase outdoor play for children from more socioeconomically disadvantaged families, but larger studies are needed to contribute to the evidence. © 2019 Elsevier Ltd
Keywords: Physical activity spaces; Outdoor play; Sedentary behavior; Children; Built environment; Natural experiment; Equity effects